Interleukin (IL)-12, IL-2, and IL-6 gene polymorphisms in Takayasu's arteritis from Turkey - DİRESKENELİ, RAFİ HANER (ELSEVIER SCIENCE INC, 2006)
Takayasu's arteritis (TA) is a chronic arterial inflammation of unknown etiology involving mainly the aorta and its major branches. Genetic polymorphisms of cytokines are screened as susceptibility factors for TA in Turkey. A total of 94 patients with TA were investigated for the genetic polymorphisms of the interleukin genes IL12, IL2,and IL6 and were compared with 108 healthy control subjects using polymerase chain reaction-sequence-specific primer method. The frequencies of IL12B 1188 C allele (p = 0.03, OR = 1.7) and CC genotype (p = 0.007, OR = 3.7) were both higher in TA patients than in control subjects. TT genotype at IL2-330 (p = 0.006, OR = 2.4) and GG genotype at IL6-174 (p = 0.04, OR = 1.9) were more frequent in TA patients. Lower prevalence of GT genotype at IL2-330 (P = 0,005, OR = 0.4), CG genotype at IL6-174 (p = 0.001, OR = 0.4), and AG genotypes at IL6-598 (p = 0.01, OR = 0.4) were also detected. The polymorphism of IL-12 as well as IL-6 and IL-2 genes may contribute to susceptibility and pathogenesis of TA by altering cytokine production and inducing inflammation. (c) American Society for Histocompatibility and Immunogenetics, 2006. Published by Elsevier Inc.
Keywords: Takayasu; IL6; IL12; IL2; polymorphism; PROMOTER POLYMORPHISM; P40 GENE; ASSOCIATION; SUSCEPTIBILITY; DISEASE; CELLS